IDA I DEWA AGUNG ISTRI KANIA: RAJA, FEMINISME, DAN PAHLAWAN DARI KLUNGKUNG - I Nyoman Sukartha (Pascasarjana Universitas Hindu Indonesia, 2016)
The feminism movement in the field of classical literature in Bali is known to rise after a female au- thor struggling from the Dutch intervention. This female figure was Ida I Dewa Agung Istri Kania. She had compiled several literary works through her criticism and â€œlangoâ€, either herself or accompanied by her pupils. The forms of her works are kakawin, kidung, geguritan, and tutur. The most popular work is Kakawin Pralambang Bhasa Wewatekan. This Kakawin tells about death body burning cere- mony (Patiwa-tiwa and Baligya). It describes the entrance of Dutch into Bali and the struggle to fight against in Kusamba, Klungkung. There is also a story concerning the memorandum of understanding between Klungkung, Gianyar, Bangli, and Payangan. These stories come along with several other sto- ries behind some factual events made in Kusamba, Sweta Lombok, Tabanan, as well as in Klungkung. It is very interesting that the phenomenal Ida I Dewa Agung Istri Kania is analyzed on the sociology of literature viewpoint. It is supposed to have significance for the younger and future generations, at least in Bali. The Balinese society must be proud of having their own hero, King, who is an author of the classical works. She is a mirror, figure to take as an example of nobleness for the nation, particularly the younger female generations.